Securing the Surgical Field in Laparoscopic Pancreatectomy Using a Penrose Drain and Endo Close. Issue 3 (June 2015) - Sunose, Yutaka; Hirai, Keitaro; Nakazawa, Seshiru; Yoshinari, Daisuke; Ogawa, Hiroomi; Tsukagoshi, Hiroshi; Takahashi, Norifumi; Yamazaki, Hodaka; Motegi, Yoko; Miyamae, Yohei; Igarashi, Takamichi; Takahashi, Kengo; et al.
<x xml:space="preserve">Abstract</x> Introduction: We adopted the use of Penrose drains and Endo Close to secure a good surgical field during laparoscopic pancreatectomy. Methods: We used a Penrose drain with threads ligated on both ends to suspend the stomach. We then pulled the threads out of the body from the side of the trocar or from besides the xiphisternum by using Endo Close. In most cases, 2 Penrose drains were used to retract the stomach. When the greater omentum on the left side of the cardia still blocks the surgical field, we sewed the posterior wall of the stomach onto the dome of the diaphragm. Results: The use of 2 Penrose drains and Endo Close were effective to retract the stomach in most cases. However, in 3 cases, we needed to additionally sew the stomach onto the diaphragm to fully open up the field. Conclusion: This is a simple and effective method to ensure a good surgical field.